Influence of Heat Treatment and High-Pressure Torsion on Phase Transformations in TiZrHfMoCr High-Entropy Alloy - Gornakova, Alena; Straumal, Boris; Kuzmin, Alexei; Tyurin, Alexander; Chernyaeva, Elena; Druzhinin, Alexander; Afonikova, Natalia; Davdian, Gregory (MDPI, 2023)
The study focused on a 21.99 at.%Ti–22.49 at.%Zr–20.35 at.%Hf–17.45 at.%Mo–17.73 at.%Cr). Analytical techniques such as X-ray diffraction, scanning electron microscopy as well as X-ray absorption spectroscopy were employed to investigate the alloy’s structure, phase transformations, and properties. The alloy in the as-cast state contained three phases, namely the body-centred cubic (A2) phase, hexagonal Laves phase (C14), and cubic Laves phase (C15). The alloy has been annealed for a long time at different temperatures. It led to the disappearance of the hexagonal Laves phase, leaving behind two primary phases, namely the cubic Laves phase (C15) and the body-centered cubic phase (A2). At 1200 °C, the A2 phase almost disappeared, resulting in a practically single-phase sample. After a high-pressure torsion (HPT) treatment, the hexagonal Laves phase disappeared entirely, while the A2 and C15 phases remained. The grain size of the A2 and C15 phases was refined after HPT and grains were elongated, and their configuration resembled a layered structure. The high hardness of the A2 and C15 + C14 phases accounted for this behavior. The lattice parameters in the A2 and C15 phases after HPT treatment approached those observed after prolonged annealing at 1000 °C, indicating that the composition of these phases after short-term high-pressure torsion at ambient temperature is equivalent to the composition of these phases after long tempering at 1000 °C. The rate of diffusion-like mass transfer during severe plastic deformation was estimated to be many orders of magnitude higher than that for conventional bulk diffusion at the HPT treatment temperature and similar to that at elevated temperatures above 1000 °C. X-ray absorption spectroscopy results obtained at K-edges of Ti, Cr, Zr, and Mo as well as at the L3-edge of Hf indicated that the local environment around metal atoms before HPT was similar to that after HPT. However, the static disorder increased after HPT, which could be attributed to an increased specific amount of metal atoms in the disordered grain boundary layers after HPT-driven grain refinement. --//-- This is an open access article Gornakova, A.; Straumal, B.; Kuzmin, A.; Tyurin, A.; Chernyaeva, E.; Druzhinin, A.; Afonikova, N.; Davdian, G. Influence of Heat Treatment and High-Pressure Torsion on Phase Transformations in TiZrHfMoCr High-Entropy Alloy. Metals 2023, 13, 1030. https://doi.org/10.3390/met13061030 published under the CC BY 4.0 licence.
This research was funded by the Russian Ministry of Science and Higher Education (contract no. 075-15-2021-945 grant no. 13.2251.21.0013).
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; high-entropy alloy; heat treatment; high-pressure torsion; Laves phases; solid solutions; XANES; EXAFS